Going to extremes – a metagenomic journey into the dark matter of life. Issue 12 (11th June 2021) - Aevarsson, Arnthór; Kaczorowska, Anna-Karina; Adalsteinsson, Björn Thor; Ahlqvist, Josefin; Al-Karadaghi, Salam; Altenbuchner, Joseph; Arsin, Hasan; Átlasson, Úlfur Áugúst; Brandt, David; Cichowicz-Cieślak, Magdalena; Cornish, Katy A S; Courtin, Jérémy; et al.
ABSTRACT: The Virus-X—Viral Metagenomics for Innovation Value—project was a scientific expedition to explore and exploit uncharted territory of genetic diversity in extreme natural environments such as geothermal hot springs and deep-sea ocean ecosystems. Specifically, the project was set to analyse and exploit viral metagenomes with the ultimate goal of developing new gene products with high innovation value for applications in biotechnology, pharmaceutical, medical, and the life science sectors. Viral gene pool analysis is also essential to obtain fundamental insight into ecosystem dynamics and to investigate how viruses influence the evolution of microbes and multicellular organisms. The Virus-X Consortium, established in 2016, included experts from eight European countries. The unique approach based on high throughput bioinformatics technologies combined with structural and functional studies resulted in the development of a biodiscovery pipeline of significant capacity and scale. The activities within the Virus-X consortium cover the entire range from bioprospecting and methods development in bioinformatics to protein production and characterisation, with the final goal of translating our results into new products for the bioeconomy. The significant impact the consortium made in all of these areas was possible due to the successful cooperation between expert teams that worked together to solve a complex scientific problem using state-of-the-art technologies as well as developing novel tools to explore the virosphere, widely considered as the last great frontier of life. Abstract : Virus-X: exploring the virosphere – the largest reservoir of unknown genetic diversity on Earth.